Excess mortality in Mexico 2020: a preliminary estimate at national and state level - Silva Urrutia, Jose Eliud (2021)
As a direct or indirect consequence of the COVID-19 pandemic, joint other public health problems, Mexico is one of the most affected countries in terms of excess mortality, which is generalized and heterogeneous at the state level. That is why, the paper’s aim is to quantify it at national and subnational level both through the percentage of excess mortality (% EM) and using differences in life expectancies (EMex)  by sex. For (EMex) , mortality tables are constructed with specific rates that are estimated through a non-parametric approach so-called controlled and segmented smoothing. The results show the greatest excesses in male population and for some states of the country. Likewise, regarding EMex, strong setbacks in life expectancy can be observed including the Mexico City.